Wykształcenie ludności rolniczej a zrównoważony rozwój Podlasia - Kołoszko-Chomentowska, Zofia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper describes the role of education in sustainable development. The aim was to estimate education level changes of rural population in Podlasie province between 1996 and 2002. The directions of the changes are quite proper and lie in significant growth of number of population with university degree and drop of population with primary education. The analysis shows that the quality of human resources improves systematically, but level of the farmers education is still low and requires working on the changes which will favour new ways of farming. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 237-241